Effectiveness Of Bacillus Spp. On Ammonia Reduction And Improvement Of Water Quality In Shrimp Hatchery - Ng, Chi Foon (2004)

(untitled)
Three Bacillus isolates, B. subtilis AB65, B. pumilus AB58 and B. liheniformis AB69 from brackish water environment were studied for their potential use in aquaculture bioremediation. In laboratory, all three Bacillus species grew well in Glucose-Ammonium-Peptone and reduced total ammonia nitrogen (TAN) effectively, however, combination of B. subtilis and B. licheniformis was the best in reducing TAN to 2.098 mg/l compared to control (without Bacillus) at 5.368 mg/l. All three Bacillus isolates significantly reduced TAN in water from shrimp culture tank as compared to the control (without Bacillus), and B. pumilus was the best in reducing TAN to 0.578 mg/l compared to control (without Bacillus) at 3.284 mg/l. Among the three agriculture products used, i.e. tapioca starch, sago starch and molasses, to enhance bioremediation, only Bacillus isolates supplemented with molasses were able to reduce TAN concentration whereby B. pumilus was the best isolate in reducing TAN to 0.92 mg/l. Experiment conducted in prototype shrimp hatchery showed that addition of carbonaceous source (sugar) reduces TAN in tanks treated with Bacillus as well as in control tanks (without Bacillus). Combination of B. pumilus and B. licheniformis with sugar was the best treatment reducing TAN to 0.05 mg/l. Overall, studies conducted in laboratory showed that B. pumilus and B. licheniformis when used as individual species were the best ammonium bioremediator whereas study conducted in shrimp hatchery showed that combination of B. pumilus and B. licheniformis was the best bioremediator. The Bacillus isolates produced extracellular enzymes protease, lipase and amylase which were of alkalophilic characteristics. The optimum condition for enzyme activity was similar to the optimum culture condition of Bacillus isolates which ranged from 30°C to 35°C and pH 7.5 to pH 9. Feed 1 (F1), Feed 2 (F2) and casein were used to elicit the production of protease and amongst the three isolates, B. licheniformis (F2) produced the highest amount of protease activity at 40.93 U/ml followed by B. pumilus (F2) at 32.82 U/ml and B. subtilis (F2) at 29.7 U/ml when assayed at pH 9. Feed 1, F2 and olive oil were used to elicit the production of lipase and lipase activity was the highest in B. licheniformis (F2) followed by B. pumilus (F1) and B. subtilis (F1) at 1.5568, 1.5338, 1.4856 U/ml respectively. Starch was used to elicit the production of amylase and only B. subtilis produced amylase at 13.5255 U/ml. The Bacillus isolates proved to be able to bioremediate ammonium and hold promising future in aquaculture bioremediation